2020
DOI: 10.1037/dev0000932
|View full text |Cite
|
Sign up to set email alerts
|

The curvilinear effect of mothers’ parenting stress and attunement on children’s internalizing symptoms: A six wave study of mother–youth dyads across the transition to adolescence.

Abstract: We aimed to test how deviations in a mother’s own parenting stress (PS) levels across her child’s transition to adolescence contribute to subsequent changes in her child’s internalizing symptom levels. We tested both linear and curvilinear effects, as well as the extent to which a child’s perception of his or her mother’s attunement alters these links. We further explored whether overall maternal PS levels (relative to the other mothers) further moderate the within-dyad association. These effects were tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 71 publications
1
14
1
Order By: Relevance
“…For example, research has shown that adults reporting mild levels of lifetime adversity exhibited lower psychological problems and stress reactivity than their counterparts who experienced either minimal or high adversity (e.g., Seery et al, 2010Seery et al, , 2013. Consistent with this research, a concurrent curvilinear link between parenting stress and adolescent internalizing symptoms corresponded with the steeling effects model and the hypothesis that youth would evidence the lowest emotional distress at moderate levels of parenting stress (Arbel et al, 2020). However, in this same study, prospective analyses failed to identify a quadratic risk effect.…”
Section: Quadratic Models Of Family Risksupporting
confidence: 80%
See 2 more Smart Citations
“…For example, research has shown that adults reporting mild levels of lifetime adversity exhibited lower psychological problems and stress reactivity than their counterparts who experienced either minimal or high adversity (e.g., Seery et al, 2010Seery et al, , 2013. Consistent with this research, a concurrent curvilinear link between parenting stress and adolescent internalizing symptoms corresponded with the steeling effects model and the hypothesis that youth would evidence the lowest emotional distress at moderate levels of parenting stress (Arbel et al, 2020). However, in this same study, prospective analyses failed to identify a quadratic risk effect.…”
Section: Quadratic Models Of Family Risksupporting
confidence: 80%
“…Although research on interparental conflict as a quadratic predictor of child functioning is limited, stress conceptualizations in the broader developmental psychopathology literature have postulated that quadratic or curvilinear risk may be expressed in two complementary ways. First, steeling effects models propose that family adversity is not necessarily harmful for children when it occurs in mild and manageable doses (Arbel et al, 2020; Repetti & Robles, 2016; Rutter, 2012). Although steeling effects models generally share the assumption that intermittent, brief, and mild stress in the family is benign for children, versions of the model differ in the degree to which exposure to these stressful events may reduce their subsequent distress and vulnerability.…”
Section: Quadratic Models Of Family Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the broader representation of SES, various family constellations, and multiple ethnic–racial groups, the link between SES and ERS may follow a curvilinear trend such that at different ends of the SES spectrum the associations differ, thereby canceling each other out in the current sample. This assumption is plausible given that similar trends are found among the links between SES and youth outcomes or parenting and youth outcomes (e.g., Arbel et al, 2020; Lei, 2017). Future studies should purposively sample families with diverse family structures and SES to better approximate the national landscape, offering a more holistic picture of these associations.…”
Section: Discussionmentioning
confidence: 75%
“…Prominent interparental conflict scholars (Davies & Sturge-Apple, 2007 ; Davies et al, 2021 ) thus have called for refinements to the classic models by underscoring that interparental conflict may not merely sensitize children’s distress and behavioral responses in the linear, dose–response manner as originally proposed. Considering a quadratic manner as suggested by the curvilinear models of risk sensitization (see Arbel et al, 2020 ; Repetti & Robles, 2016 ; Susman, 2006 ) may constitute a promising direction for future research in this field. To our knowledge, no study has tested such patterns specifically in divorce families, but research based on intact families has been emerging during the recent years (e.g., Davies et al, 2020 , 2021 ).…”
Section: Children’s Perceptions and Feelingsmentioning
confidence: 99%